2016
DOI: 10.1186/s12889-016-3058-1
|View full text |Cite
|
Sign up to set email alerts
|

Internet use and electronic gaming by children and adolescents with emotional and behavioural problems in Australia – results from the second Child and Adolescent Survey of Mental Health and Wellbeing

Abstract: BackgroundConcerns have been raised of a potential connection between excessive online activity outside the academic realm and increased levels of psychological distress in young people. Young Minds Matter: the second Australian Child and Adolescent Survey of Mental Health and Wellbeing provides estimates of the prevalence of online activity and allows an exploration of associations between this activity, a range of mental disorders, socio-demographic characteristics and risk taking behaviour.MethodsBased on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 77 publications
(95 reference statements)
6
93
0
7
Order By: Relevance
“…Evidence exists for the unique experiences of mental health for male and females and defining such differences is another critical aspect of this research. The associations between problematic Internet use (addiction) and mental disorders among Australian adolescents has recently been reported [17]. However the relationship between duration of time spent online (spanning low to high users) and mental health status requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence exists for the unique experiences of mental health for male and females and defining such differences is another critical aspect of this research. The associations between problematic Internet use (addiction) and mental disorders among Australian adolescents has recently been reported [17]. However the relationship between duration of time spent online (spanning low to high users) and mental health status requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also reported PGB to be associated with greater impulsivity (Kim et al, 2016b;Walther et al, 2012), poorer self-control (Kim et al, 2008), increased attention deficit (Andreassen et al, 2016;Gentile, 2009;Müller et al, 2015;Walther et al, 2012), hyperactivity (Baer et al, 2012;Rikkers et al, 2016;Strittmatter et al, 2015), concentration prob-lems (Kim et al, 2016b), augmented self-dis-crepancy (Kwon et al, 2011), lower self-esteem (Festl et al, 2013;Lemmens et al, 2015;Papay et al, 2013;Van Rooij et al, 2012;Walther et al, 2012), impaired life skills (Baer et al, 2012) and low school well-being (Rehbein and Baier, 2013). Wan and Chiou (2006) reported that dissatisfaction concerning safety, love, belonging, self-esteem and self-actualisation were key risk factors for PGB.…”
Section: Pgb: Health-related Outcomesmentioning
confidence: 99%
“…Additionally, PGB was found to be positively associated with the following outcomes: attentiondeficit hyperactivity disorder (ADHD; Andreassen et al, 2016), psychoticism (Starcevic et al, 2011), obsessive-compulsive disorder (OCD;Andreassen et al, 2016;Kim et al, 2016b;Starcevic et al, 2011;Vukosavljevic-Gvozden et al, 2016), obsessive passion disorder (Lafreniere et al, 2009) and general psychiatric distress (Király et al, 2015;Rikkers et al, 2016). One study (Li et al, 2011) reported that gamers exhibiting greater actual-ideal self-discrepancy and depression were more likely to present with higher levels of escapism and PGB symptoms.…”
Section: Pgb: Health-related Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…There may also be risks faced by children whose brains are still developing, particularly those with neurodevelopmental disorders, such as attention deficit/hyperactivity disorder, autism or schizophrenia. 10 With thinner skulls, the amount and frequency of stimulation applied to a child's brain could potentially have a much greater adverse effect. 11 This is particularly troubling given evidence that shows that home users of tDCS devices, such as children involved in online gaming, often use higher currents for extended periods of time.…”
Section: Safety Concernsmentioning
confidence: 99%